A A Pilot Study of Utilization of Blood Components at Tertiary Care Centre, Rajkot - Katkoria, Shruti K; Agravat, Amit H; Dhruva, Gauravi A (Annals of Pathology and Laboratory Medicine, 2018)
Background: Blood is essential for life. It contains cellular component and plasma which supplies oxygen, nutrients to different parts of the body. Transfusion of blood and blood components is an integral part of health care practice. Many a times there will be injudicious use of blood and its products among patients which causes unnecessary burden to the patients as well to blood bank. Main aim of this study is to evaluate the pattern of utilization of blood component in tertiary care hospital at Rajkot Methods: This was retrospective study carried out over a period of 1 year from January 2017 to December 2017. All the data were collected from blood bank. Result: Total number of the blood components utilized in the year 2017 was 22290.The most utilized blood component included of Red Cell Concentrate (RCC) followed by Fresh Frozen Plasma (FFP) and Platelet Concentrate respectively .Cryoprecipitate was least utilized component. Thalassemia ward was majorly benefited. Conclusion: Periodic evaluation of utilization pattern, demand for different blood products also helps to maintain the blood stock.